Self-Medication and Outpatient Care Utilization after Implementation of National Health Insurance in Indonesia - Via Dolorosa Halilintar; Amal Chalik Sjaaf (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The implementation of National Health Insurance in 2014 is expected to increase access in health services while reducing the economic burden due to illness. This study aims to see how the behavior of people in choosing treatment when experiencing health problems, whether they tend to select self-medication or outpatient treatment. Quantitative analysis was carried out on variables previously formed based on the KOR Data questionnaire found in SUSENAS 2017. The results of the study showed that more respondents chose to do self-medication than those who accessed formal services with outpatient care. Multivariate tests show all variables except secondary education significantly influence individual decisions to self-medication.